2010
DOI: 10.1007/s00109-010-0619-0
|View full text |Cite|
|
Sign up to set email alerts
|

TRAIL signaling is mediated by DR4 in pancreatic tumor cells despite the expression of functional DR5

Abstract: Tumor necrosis factor related apoptosis-inducing ligand (TRAIL) and agonistic anti-DR4/TRAIL-R1 and anti-DR5/TRAIL-R2 antibodies are currently under clinical investigation for treatment of different malignancies. TRAIL activates DR4 and DR5 and thereby triggers apoptotic and non-apoptotic signaling pathways, but possible different roles of DR4 or DR5 in these responses has poorly been addressed so far. In the present work, we analyzed cell viability, DISC formation as well as IL-8 and NF-kappaB activation side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 35 publications
(54 reference statements)
9
70
1
Order By: Relevance
“…DAPI staining validates increased induction of apoptosis after combined treatment especially with 15d-PGJ 2 in parental and drug-resistant HEYs with exception of the partial TRAIL-resistant docetaxel-resistant and the TRAIL-resistant control cells be accomplished by the gemcitabine-resistant subclone that showed stronger expression of DR4 compared to DR5 indicating that apoptosis is most likely induced via DR4 in these TRAIL-sensitive cells. Recently, a higher sensitivity to TRAIL was addressed to a higher expression of DR4 in colon cancer and pancreatic tumor cells (Sussman et al 2007;Lemke et al 2010). The lack of correlation between the expression of death and decoy receptors and the sensitivity of the various HEY subclones may be explained by an autocrine production of a soluble decoy receptor by resistant cells, e. g., osteoprotegerin (OPG), a member of the TNF receptor family, that competes for TRAIL binding providing a mechanism for protection against apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…DAPI staining validates increased induction of apoptosis after combined treatment especially with 15d-PGJ 2 in parental and drug-resistant HEYs with exception of the partial TRAIL-resistant docetaxel-resistant and the TRAIL-resistant control cells be accomplished by the gemcitabine-resistant subclone that showed stronger expression of DR4 compared to DR5 indicating that apoptosis is most likely induced via DR4 in these TRAIL-sensitive cells. Recently, a higher sensitivity to TRAIL was addressed to a higher expression of DR4 in colon cancer and pancreatic tumor cells (Sussman et al 2007;Lemke et al 2010). The lack of correlation between the expression of death and decoy receptors and the sensitivity of the various HEY subclones may be explained by an autocrine production of a soluble decoy receptor by resistant cells, e. g., osteoprotegerin (OPG), a member of the TNF receptor family, that competes for TRAIL binding providing a mechanism for protection against apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…TRAIL and CD95L cannot only induce apoptosis but also proinflammatory, proliferative, and promigratory signals (Ehrhardt et al 2003;Budd et al 2006;Peter et al 2007;Wilson et al 2009;Lemke et al 2010;Roder et al 2011). Some of these signals occur in a FADD/caspase-8-independent manner but the mechanisms are still debated (Green 2010).…”
Section: Integrating Cell Death and Inflammationmentioning
confidence: 99%
“…32,33 Increased number of MSC-mediated anticancer studies have shown MSCs to be an effective therapeutic tool and gene carrier for the treatment of pancreatic cancer. 34 To use MSCs as effective anticancer agent vehicles, we need a viable and practical source of MSCs and a method to successfully transfect MSCs with anticancer genes.…”
Section: Dynamic Observation Of Msc Migration Toward Pancreatic Cancementioning
confidence: 99%